MicroRNAs in the regulation of immune cell functions – implications for atherosclerotic vascular disease - Zernecke, Alma (Thrombosis and Haemostasis, 2012)
Regarded as a chronic inflammatory disease of the vessel wall, the development of atherosclerotic lesions is shaped by immune responses and their regulation. Macrophages and dendritic cells are positioned at the crossroad of innate and adaptive immune responses by sensing atherogenic danger signals and by taking up and presenting antigens. T helper cells and auto-antibodies produced by B cells, together with their cytokine responses in turn modulate atheroprogression. In addition, platelets contribute to atherosclerosis by multiple pathways. microRNAs (miRNAs) that post-transcriptionally regulate gene expression may thus critically control immune cell differentiation and functions during plaque evolution. This review summarises the role of miRNAs in regulating lipid uptake and expression of inflammatory mediators in monocytes/macrophages and dendritic cells, in lymphocyte functions with a focus on T helper cell responses, as well as in platelet biology, and the implications of altering these functions in vascular pathology and atherosclerosis. T systematically survey miRNA functions in controlling molecular mechanisms and immune responses in atherosclerosis holds potential for the development of novel miRNA-based strategies for therapies targeting inflammation and immunity in atherosclerosis.
Keywords: microRNAs; inflammation; immune cells; remodelling; atherosclerosis